Cursed consumers and the effectiveness of consumer protection policies - Alessandro Ispano; Peter Schwardmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We model firms' quality disclosure and pricing in the presence of cursed consumers, who fail to be sufficiently skeptical about undisclosed quality. We show that cursed consumers are exploited in duopoly markets if firms are vertically differentiated, if there are few cursed consumers, and if average product quality is high. Three common consumer protection policies that work under monopoly, i.e. mandatory disclosure, third party disclosure and consumer education, may all increase exploitation and decrease welfare. Even where these policies improve overall welfare, they often lead to a reduction in consumer surplus. We show that our conclusions hold in extensions with endogenous quality choice and horizontal differentiation.
Keywords: C72; D03; D82; D83; 330; naive; cursed; disclosure; consumer protection; labeling; competition